PEMANFAATAN MEDIA PEMBELAJARAN PAPAN HURUF UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF : Mengenal huruf, Media papan huruf, Pembelajaran. - Nafsia, Andi; Sanda, Eusabia; Soa, Maria Moi; Nona, Maria Onita (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2024)
Introduction to the school field is a program that aims to determine childen’s ability to recognize letters. In PLP 1 activities,one of the activities carried out is observing learning activities in class using learning media. The learning media observed was the use of letter board media. The aim is to determine the benefits of letter board media in increasing letter recognition in early childhood. This activity was carried out at TKK EFATA BOBA. The method used in implementing the activity was descriptive qualitative. Data collection techniques were carried out using observation,interviews and documentation techniques. This activity was carried out on March 14 2024 at TKK EFATA BOBA with a total of 18 children,9 boys and 9 girls. The result of this activity is that the children at TKK EFATA BOBA have learned letters and there are also some children who do not know letters well.